The Gravity Equation in International Trade: A Note - Dewitte, Ruben (Journal of Political Economy, 2022)
Chaney (2018) presents an intuitive, dynamic model of firm-to-firm trade that defines the functional relationship between aggregate trade and distance x under three conditions: if (i) firm size K P areto(K min , ) with shape parameter 1 for all firms,